2021
DOI: 10.1002/pssa.202000558
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic Study of Bovine Serum Albumin Adsorption on Zinc Oxide (0001) Surface

Abstract: Properties and functions of various ZnO materials are intensively investigated in biological systems for diagnostics, therapy, health risks assessment as well as bactericidal and decontamination purposes. Herein, the interface between ZnO and biological environment is studied by characterizing adsorption of bovine serum albumin (BSA) and fetal bovine serum (FBS) using atomic force microscopy with CF4‐treated tips. Similar molecular morphologies (thickness around 2 nm) yet different binding forces to ZnO (10–25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…To analyze not only the topography but also the adhesion of the BSA molecules, we employed nanoshaving experiments. They have been previously well proven in studies of DNA molecules grafted on diamond, [46] BSA molecules adsorbed on plasma polymer coating, [47] on diamond [48] and on ZnO (0001) surface [39] . Hereby, we perform them on the BSA to analyze the layer thickness and adhesion properties of BSA layers on various ZnO surfaces.…”
Section: Methodsmentioning
confidence: 98%
See 2 more Smart Citations
“…To analyze not only the topography but also the adhesion of the BSA molecules, we employed nanoshaving experiments. They have been previously well proven in studies of DNA molecules grafted on diamond, [46] BSA molecules adsorbed on plasma polymer coating, [47] on diamond [48] and on ZnO (0001) surface [39] . Hereby, we perform them on the BSA to analyze the layer thickness and adhesion properties of BSA layers on various ZnO surfaces.…”
Section: Methodsmentioning
confidence: 98%
“…FF calculations were performed to determine the most likely orientation of BSA over different ZnO surfaces. We used same FF methodology as in our recently published papers [39,40] . Briefly, the systems under the study consist of BSA molecules and ZnO slabs that are available from the RCSB Protein Data Bank (pdb ID of 4F5S) and QuantumATK software database respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The AFM observations were corroborated by atomic-scale simulations of BSA on the (0001) ZnO surface using the force-field method and showing rearrangements of Zn surface atoms. 31 …”
Section: Resultsmentioning
confidence: 99%
“…Thus, their behavior in the colloid as well as inherent properties can be suppressed or enhanced by surface interaction with other molecules that are also present in the liquid such as proteins or carbohydrates. Our prior computer simulations showed that the interaction between amino acids and zinc oxide surface involved covalent bonding and not merely due to passive adsorption [8].…”
Section: Introductionmentioning
confidence: 97%